AGN feedback and galaxy evolution in nearby galaxy groups using CLoGS. Issue Volume 15:Issue S359(2020) (March 2019) - Kolokythas, Konstantinos
Abstract: Much of the evolution of galaxies takes place in groups where feedback has the greatest impact on galaxy formation and evolution. We summarize results from studies of the central brightest group early-type galaxies (BGEs) of an optically selected, statistically complete sample of 53 nearby groups (<80 Mpc; CLoGS sample), observed in radio 235/610 MHz (GMRT), CO (IRAM/APEX) and X-ray (Chandra and XMM-Newton) frequencies. We characterize the radio-AGN population of the BGEs, their group X-ray environment and examine the jet energetics impact on the intra-group gas. We discuss the relation between the radio properties of the BGEs and their group X-ray environment along with the relation between the molecular gas content and the star formation that BGEs present. We conclude that AGN feedback in groups can appear as relatively gentle near-continuous thermal regulation, but also as extreme AGN activity which could potentially shut down cooling for longer periods.